2013
DOI: 10.11648/j.ajls.20130104.11
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Virus and Hepatitis C Virus in Healthcare Workers - AIMS, B G Nagara

Abstract: Abstract:Healthcare workers have an elevated risk of acquiring and transmitting parental infections. The purpose of this study was to determine the seroprevalence of HBV and HCV among the health care workers. One hundred and sixty eight HCWs (doctors-6, nurses-38, technicians-10, ward attenders-91, nursing students-23) were screened for HBsAg. These HCWs were not vaccinated against hepatitis B virus infection. Among them, two (1.19%) were positive for HBsAg. The positive persons were ward attenders (1 male, 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…MWH with greater than 10 years of service appeared to be more affected by HBV compared to those with 1 years to 5 years of service, although the difference was not statistically significant. Previous studies of HCW indicate that the risk of exposure to HBV infection increases with longer service years [ 10 , 11 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…MWH with greater than 10 years of service appeared to be more affected by HBV compared to those with 1 years to 5 years of service, although the difference was not statistically significant. Previous studies of HCW indicate that the risk of exposure to HBV infection increases with longer service years [ 10 , 11 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…MWH with greater than 10 years of service appeared to be more affected by HBV compared to those with 1 years to 5 years of service, although the difference was not statistically significant. Previous studies of HCW indicate that the risk of exposure to HBV infection increases with longer service years [10,11,16,17]. Several other factors, such as prior blood transfusion, needle stick injuries, lack of training in infection prevention, and not being vaccinated, have been reported to increase the risk of HBV infection [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence of hepatitis B surface antigen (HBsAg) among HCW was reported to be 8.1% in Uganda [8] and 9.7% in Ethiopia [9]. It was also reported that medical waste handlers (MWH) are more exposed to HBV infection than other HCW [10], non-medical waste handlers (NMWH) [11,12], or the general population [6]. Indirect inoculation through improperly collected and/or segregated sharp materials is considered to be an occupational hazard for MWH in health institutions, compared to NMWH or the proportion of the general population that has no direct or indirect contact with medical waste [6,12].…”
Section: Introductionmentioning
confidence: 99%